Macrococcus caseolyticus in early-onset neonatal sepsis, Kassala, Sudan - Musa, Abdualmoneim O; Santona, Antonella; Desogi, Mohamed AA; Fiamma, Maura; Adam, Ali; Ibrahim, Duaa H; Hajedriss, Faiza A; Almake, Fatima A; Faki, Mahmoud T; Awadap, Mohamed I; Taviani, Elisa; Rubino, Salvatore; et al. (The Journal of Infection in Developing Countries, 2025)
Introduction: Neonatal sepsis, a clinical syndrome characterized by systemic signs of infection in newborn infants (< 28 days old), are a significant cause of neonatal mortality and long-term morbidity globally, particularly in low- and middle- income countries. Case presentation: We report the first case of neonatal sepsis caused by Macrococcus caseolyticus in a 48-hours old newborn who attended to the intensive care unit (ICU) of the Kassala Specialized Hospital for Pediatrics in Sudan, with signs of severe bacterial infection. M. caseolyticus is an opportunistic pathogen normally associated with veterinary and food-borne infections. Empirical antibiotic therapy was promptly initiated following blood sampling and culture, resulting in recovery within 4 days. M. caseolyticus was identified by mass spectrometry and confirmed by whole genome sequencing. The isolated strain, KaM20, was resistant to tetracycline, due to the presence of the tet(L) gene; and harbored several virulence-associated genes. Phylogenetic analysis including M. caseolyticus genomes from the GenBank suggested an animal origin for KaM20. Conclusions: This case presents a rare instance of neonatal sepsis caused by M. caseolyticus; indicating potential zoonotic transmission of this pathogen, through maternal or environmental exposure to animals in the rural household. The findings emphasize the need for increased awareness of zoonotic infections in neonatal care, particularly in regions where exposure to animals is common; and underscore the importance of understanding the complex interplay between host factors, environmental exposures, and microbial pathogens, in the development of neonatal sepsis; reinforcing the need of a 'One Health' approach in addressing emerging infectious diseases.